PERISTILAHAN ADAT MENDIRIKAN RUMAH MASYARAKAT MELAYU SINTANG KELURAHAN MENGKURAI - Arif, Nurul Latifah; Muzammil, Ahmad Rabi?ul; Muzammil, Ahmad Rabi?ul; Syahrani, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTerms in building houses of Malay people in Sintang Mengkurai village is aimed at basing the tradition as to preserve the knowledge about the terms in the culture. The problem of this research is lingual units and the significance of the terms in building houses, and the supplementary teaching material in Indonesian Language learning on year-7 in the curriculum of 2013 regarding the terms in building houses of Malay people in Sintang.This research adoped descriptive method through qualitative study and the approach was ethnolinguistics approach. Based on the data analysis, the researcher drawed the following conclusions; (a) lingual units (b) lexical and cultural meaning (c) supplementary teaching material of Indonesian language learning on the standard competence 4.1 in the curriculum of 2013 in the second semester of the year-7 of Junior High School. The researcher found at least 69 terms in which for the first problem there were certain form of lingual units of the terms used by Malay People of Sintang in building houses. First, there were 30 lexemes. Second, the polymorphous lexicon was affixation by which is dominated by the affix in the beginning of root words which is 1. Third, lexical nominee in form of phrases by which were dominated by exocentric are there 38 lexemes.  Keywords: Terms, Culture Of Building Houses